2018
DOI: 10.1002/pds.4657
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal function with long‐term exposure to antiretroviral therapy in HIV‐infected adults in Asia

Abstract: Introduction: Renal disease is common amongst people living with HIV. However, there is limited information on the incidence and risk factors associated with renal dysfunction among this population in Asia. Methods: We used data from the TREAT Asia HIV Observational Database. Patients were included if they started antiretroviral therapy (ART) during or after 2003, had a serum creatinine measurement at ART initiation (baseline) and had at least two follow-up creatinine measurements taken ≥3 months apart. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…(90) country study and it still showed the increasing loss in eGFR in the TDF group compared to the non-TDF group (41). On the other hand, a single-center study from Montreal, Canada reported that among 1043 patients mostly comprised of Whites, there was no trend between the years of exposure and the loss in eGFR in the TDF group relative to non-TDF group (15).…”
Section: Tenofovir Nephrotoxicity For Asians Living With Hiv Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…(90) country study and it still showed the increasing loss in eGFR in the TDF group compared to the non-TDF group (41). On the other hand, a single-center study from Montreal, Canada reported that among 1043 patients mostly comprised of Whites, there was no trend between the years of exposure and the loss in eGFR in the TDF group relative to non-TDF group (15).…”
Section: Tenofovir Nephrotoxicity For Asians Living With Hiv Infectionmentioning
confidence: 99%
“…Although evidence is still limited to draw any firm conclusions, it is interesting that two observational studies from Asia showed that the loss in eGFR among the patients who started TDF-containing ART relative to that in those who started non-TDF-containing ART continued to increase over time (20,41), whereas one cohort study from Canada did not show such finding and concluded that most of the loss in eGFR was acquired during the first year of exposure and stabilized after that (15) (Figure 2). In the Japanese cohort study, the loss in eGFR in the TDF group relative to the ABC group continuously increased over time, and reached -10.3 mL/min/1.73 m 2 at 5 years of TDF exposure (20) (Figure 2).…”
Section: Tenofovir Alafenamidementioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Studies have consistently demonstrated that TDF is associated with a decline of eGFR and renal dysfunction in a subpopulation. [9][10][11][12][13][14] Delineating exactly the eGFR progression trajectories on TDF therapy through routine screening is undoubtedly helpful in this scenario. Since a linear figure seems convenient to interpret, most of the relevant studies so far considered the decline of eGFR to be approximately linear.…”
Section: Introductionmentioning
confidence: 99%